Wheat Allergy and Intolerence; Recent Updates and Perspectives. Issue 1 (2nd January 2016) - Pasha, Imran; Saeed, Farhan; Sultan, Muhammad Tauseef; Batool, Rizwana; Aziz, Mahwash; Ahmed, Waqas
Abstract : The current review paper highlights the complicacies associated with communities relying on wheat as their dietary staple. Although, wheat is an important source of nutrients but is also linked with allergenic responses in genetically susceptible subjects. The wheat proteins especially α-amylase inhibitors, ω-5 gliadins, prolamins, nonprolamin, glucoprotein, and profilins are of significance importance. The allergenic responses are further categorized into IgE-mediated and non-IgE-mediated reactions. Conjugation and degranulation of the IgEs with the allergens results in release of several mediators. In contrary, non-IgE-mediated wheat allergy depends on immune complexes formed by food and food antibodies and cell-mediated immunity. As results, different diseases tend to occur on the completion of these reactions, i.e., celiac disease, baker's asthma, diarrhea, atopic dermatitis, and urticaria. This instant paper highlighted the concept of food allergy with special reference to wheat. The models are developed that are included in this paper showing the wheat allergen, their possible routes, impact on human health, and indeed possible remedies. The paper would provide the basic information for the researchers, common man, and allied stakeholders to cater the issue in details. However, the issue needs the attention of the researchers as there is a need to clarify the issues of wheat allergy and wheat intolerance.